Pertussis in a child of the first month of life from family contact - O. V. Iozefovich; S. M. Kharit; E. I. Bobova; E. A. Budnikova (Журнал инфектологии)
A case of whooping cough in a moderate form in a child of the first month of life is described in the presented clinical observation. The moderate form was manifested by the duration of the preconvulsive period up to 5 days, the appearance of cyanosis of the face when coughing in the early stages of the disease (1 week), an increase in the number of coughing attacks. The difficulties of treating pertussis in young children are demonstrated by our observation of the course of the disease. There is no vaccination against pertussis in children in the family due to the refusal of parents and children with prolonged coughing were not examined at the outpatient stage. As a result, chemoprophylaxis was not performed on time and the newborn was discharged from the hospital to the center of pertussis infection. The solution to the problem of reducing the incidence in children in the first months of life should be vaccination of pregnant women in the last stages, and vaccination of the environment, including agerelated revaccinations.